2007
DOI: 10.1073/pnas.0702733104
|View full text |Cite
|
Sign up to set email alerts
|

Local initiation of caspase activation in Drosophila salivary gland programmed cell death in vivo

Abstract: Programmed cell death, or apoptosis, is an essential event in animal development. Spatiotemporal analysis of caspase activation in vivo could provide new insights into programmed cell death occurring during development. Here, using the FRET-based caspase-3 indicator, SCAT3, we report the results of live-imaging analysis of caspase activation in developing Drosophila in vivo. In Drosophila, the salivary gland is sculpted by caspase-mediated programmed cell death initiated by the steroid hormone 20-hydroxyecdyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 29 publications
(37 reference statements)
0
53
0
Order By: Relevance
“…Animals which lack the EcR/USP binding element in the dronc promoter do not express dronc in the salivary gland. Additionally, caspase activation occurs in a distinct pattern in salivary glands from the anterior at 12h APF to the posterior (Takemoto et al, 2007). However, caspase activation does not follow this pattern when salivary glands are exposed to ecdysone ex vivo, but occurs anteriorally to posteriorally when ecydsone is applied to media at the anterior region of the larval salivary glands.…”
Section: Salivary Glandsmentioning
confidence: 99%
“…Animals which lack the EcR/USP binding element in the dronc promoter do not express dronc in the salivary gland. Additionally, caspase activation occurs in a distinct pattern in salivary glands from the anterior at 12h APF to the posterior (Takemoto et al, 2007). However, caspase activation does not follow this pattern when salivary glands are exposed to ecdysone ex vivo, but occurs anteriorally to posteriorally when ecydsone is applied to media at the anterior region of the larval salivary glands.…”
Section: Salivary Glandsmentioning
confidence: 99%
“…For example, the FRET-based reporters suffer from weak signals (within several tens percentage change of fluorescence) and require tedious image processing to obtain the ratiometric signal (33). A fluorophore translocation-based reporter was also developed, in which the fluorophore is anchored to plasma membrane and upon caspase cleavage it moves into nucleus, which limits its detection to early phase of apoptosis when there is little cell shape change (34).…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 99%
“…Here, to verify the existence of a relationship between LEC apoptosis and histoblast proliferation, we studied the spatiotemporal pattern of LEC apoptosis by live imaging analysis and developed a system to assay the effect of histoblast proliferation on LEC apoptosis in living animals. We previously reported a genetically encoded fluorescence resonance energy transfer (FRET)-based caspase-3 indicator, SCAT3, which enables the quantitative monitoring of caspase-3-like DEVDase activity (25,30,31,33,34,63,64). By monitoring caspase activation during the epithelial replacement in vivo at singlecell resolution, we characterized the activation of caspase in LECs and found that it is regulated by the interactions of the LECs with proliferating histoblasts.…”
mentioning
confidence: 99%